The role of the bone microenvironment in regulating myeloma residual disease and treatment - Dadzie, Terry G.; Green, Alanna C. (Frontiers in Oncology, 2022)
Multiple myeloma is an incurable haematological cancer. The increase in targeted therapies has improved the number of myeloma patients achieving a complete response and improved progression-free survival following therapy. However, a low level of disease or minimal residual disease (MRD) still persists which contributes to the inevitable relapse in myeloma patients. MRD has been attributed to the presence of dormant myeloma cells and their subsequent reactivation, which is controlled by the microenvironment and specialised niches within the bone marrow. This contributes to the evasion of the immune system and chemotherapy, eventually leading to relapse. The growth of myeloma tumours are heavily dependent on environmental stimuli from the bone marrow microenvironment, and this plays a key role in myeloma progression. The bone microenvironment also plays a critical role in myeloma bone disease and the development of skeletal-related events. This review focuses on the bone marrow microenvironment in relation to myeloma pathogenesis and cancer dormancy. Moreover, it reviews the current therapies targeting the bone microenvironment to treat myeloma and myeloma bone disease. Lastly, it identifies novel therapeutic targets for myeloma treatment and the associated bone disease.